2009
DOI: 10.1371/journal.pone.0007858
|View full text |Cite
|
Sign up to set email alerts
|

In-Group Conformity Sustains Different Foraging Traditions in Capuchin Monkeys (Cebus apella)

Abstract: BackgroundDecades of research have revealed rich cultural repertoires encompassing multiple traditions in wild great apes, a picture crucially complemented by experimental simulations with captive apes. Studies with wild capuchin monkeys, the most encephalized simian species, have indicated a New World convergence on these cultural phenomena, involving multiple traditions and tool use. However, experimental studies to date are in conflict with such findings in concluding that capuchins, like other monkeys, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 46 publications
8
63
0
2
Order By: Relevance
“…The same foraging box used by Dindo et al [11,15] was used in the present study. In this box, an opaque door could either be slid or lifted (figure 2).…”
Section: (B) Apparatusmentioning
confidence: 99%
“…The same foraging box used by Dindo et al [11,15] was used in the present study. In this box, an opaque door could either be slid or lifted (figure 2).…”
Section: (B) Apparatusmentioning
confidence: 99%
“…In recent years, majority influence has become a favourable research topic for behavioural biologists. One line of research has focused on our closest living relatives, the nonhuman primates (chimpanzees, Pan troglodytes: Bonnie, Horner, Whiten, & de Waal, 2007;Haun, Rekers, & Tomasello, 2012;Hopper, Schapiro, Lambeth, & Brosnan, 2011;Whiten, Horner, & de Waal, 2005; capuchin monkeys, Cebus apella: Dindo, Thierry, & Whiten, 2008;Dindo, Whiten, & de Waal, 2009;Perry, 2009), which could enable intriguing analysis of the evolutionary roots of this human phenomenon (MacLean et al, 2012). Another line of research has aimed to investigate the possibility of convergent evolution of conformity by focusing on phylogenetically more distant species, such as fish (Day, MacDonald, Brown, Laland, & Reader, 2001;Kendal, Coolen, & Laland, 2004;Pike & Laland, 2010), rats (Galef & Whiskin, 2008;Jolles, de Visser, & van den Bos, 2011;Konopasky & Telegdy, 1977) and fruit flies (Battesti, Moreno, Joly, & Mery, 2012).…”
mentioning
confidence: 99%
“…Later studies employed a two-action method in which an artificial fruit could be opened in one of two ways, and two groups of experimental subjects were exposed to a demonstrator who opened it in only one way. Custance et al's [14] study of human-reared capuchins and human demonstrators produced mixed results, whereas a more recent set of two-action studies, using a transmission chain design in which capuchins observed other capuchins, found much firmer evidence for faithful transmission [15,16]. These researchers drew on the idea that the quality of social relationship between the demonstrator and the observer will affect the fidelity of transmission, such that dyads with close affiliative relationships will have an inherent desire to behave similarly (i.e.…”
Section: Social Learning Of Food-processing Techniques: Experimental mentioning
confidence: 99%